Формування позитивної мотивації на здоровий спосіб життя у дітей та молоді в контексті вивчення шкільного предмета «Основи здоров’я» - Карпюк, Роман; Karpiuk, Roman; Петрик, Омелян; Petrik, Omelian (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статі запропоновано методику формування позитивної мотивації на здоровий спосіб життя у початковій та загальноосвітній школі в дітей та молоді в контексті вивчення шкільного предмета «Основи здоров’я» шляхом здійснення структурних змін у навчально - виховному процесі: співпраця колективу школи з батьківським комітетом, учнівським самоврядуванням зосередження уваги учнів на особистому та соціальному значенні здорового способу життя та мотивації на здоровий спосіб життя. The article presents the methods of formation of positive motivation for healthy lifestyles in elementary and secondary school in children and young people in the context of studying school subject "Health Basics" by structural changes in education – teaching process of collective cooperation of school parent councils, student government focus students on personal and sosial significance of healthy lifestyle and motivation for a healthy lifestyle. The most important pedagogical conditions that promote a healthy lifestyle, motivation – value relationship to the personal factor that plays a special role in the formation of a healthy lifestyle, organisation of training – educational process by improving the curriculum by including valeological of knowledge and skills, the need to focus efforts on developing a positive attitude on the part of society to educational institutions at various levels as those aimed at, along with other tasks, to teach children and young people to be healthy, wider deeper and develop prevention work among young people, especially among children and adolescents.
Formation of positive motivation for healthy lifestyle among children and youth in the context of the study of school subject "Health Basics"
Keywords: позитивна мотивація; здоровий спосіб життя; медичні знання; positive motivation; healthy lifestyle; medical knowladge